KARAKTERISASI SIFAT FISIKO-KIMIA DAN FUNGSIONAL ISOLAT PROTEIN BIJI KECIPIR (Psophocarpus tetragonolobus L.) [Characterization of Physicochemical and Functional Properties of Winged-Bean (Psophocarpus tetragonolobus L.) Protein Isolate] - Slamet Budijanto; Azis Boing Sitanggang; Wita Murdiati (Jurnal Teknologi dan Industri Pangan, 2011)
Winged-bean (Psophocarpus tetragonolobus L.) has similar protein concentration to soybean. Higher productivity of winged-bean as compared to soybean and ground nut makes it feasible to develop this legume as a natural source of vegetable protein. Protein isolate was made by isolating protein from defatted winged-bean flour employing its isoelectric point, and several stages of centrifugation. The protein content of winged-bean protein isolate was 83.87% (db). Analysis of physicochemical properties of winged-bean protein isolate, suggested that the bulk density was 0.60 g/ml with water and oil absorption capacity of 2.61 g H2O/g solid; 1.60 ml oil/g solid, respectively. Moreover, this protein isolate had emulsion capacity of 70.5%; foam capacity of 89.5% and formed gel at concentration of 15%. Data on amino acids composition indicated that glutamic acid was the highest concentration (6.37%), whereas tryptophan was the lowest one (0.37%). Several essential amino acids, such as leucine dan lysine, were found in winged-bean protein isolate at a  concentration of 3.2% and 2.8%, respectively, calculated from the total amino acid.